Role of Jamaat E Islami in Kp Provincial Assembly (2013-2018): Critical Analysis - Saqfa Jadoon; Dr Muhammad Rizwan; Sadaf Butt (Social Science Review Archives, 2025)
This research analyzes Jamaat-e-Islami's (JI) performance in the Khyber Pakhtunkhwa (KP) Provincial Assembly between 2013 and 2018, focusing on its contribution to governance and policy-making. Analyzing JI's role in KP politics gives an understanding of the dynamics of coalition politics and the role of Islamist parties in governance. Based on a qualitative case study method, examining JI's performance in the KP Provincial Assembly through document analysis, literature review, and expert opinions, this research establishes that JI's presence in the coalition government and its focus on Islamic values and social justice helped it have an impact on KP politics. In spite of its difficulties in pushing its agenda, JI's robust organizational setup and lobbying efforts helped it influence policy choices. The research emphasizes the importance of representative and advocacy-driven change to implement positive change and ensure social justice, adding to the knowledge regarding Islamist parties' roles in the government and policymaking, as well as serving as a contribution to policymakers, researchers, and stakeholders in understanding Pakistani politics. Drawing from JI's experience within the KP Provincial Assembly, this study seeks to achieve a qualitative comprehension of Pakistani political complexities as well as Islamist party roles towards developing the nation. The discoveries within this research are significant towards Islamist party study as well as how they can serve in the state, and form part of the debate as to whether or not religion belongs in politics.